OX-40 signaling promotes tumorigenesis in CTCL by regulating ERK activation - Papadavid, Evangelia; Karagianni, Fani; Vetsika, Eleni-Kyriaki; Valero-Díaz, Sara; Córdova-Hernández, Saire Edith; Daniil, Christos; Piperi, Christina; Casar, Berta (Frontiers in Immunology, 2025)
IntroductionIn Cutaneous T-cell Lymphoma (CTCL), T cells can be activated either by cytokines produced by malignant T cells or through immunological synapses, such as the interaction between OX-40 and OX-40L on dendritic cells. Both are co-expressed in tumor cells in Mycosis fungoides/Sézary syndrome and correlate with disease severity markers. Using a model of spontaneous metastasis in chick embryos, the present study aimed to determine the functional role of OX-40 in CTCL and assess its potential as a therapeutic target.MethodsOX-40 knockout MyLa and SeAx CTCL cells using CRISPR-Cas9 were engrafted onto the chorioallantoic membrane of chick embryos. We assessed tumor growth, dissemination, and TME modulation in the presence or absence of macrophages. Transwell-based transendothelial migration assays and co-culture experiments were performed to further explore the interactions between CTCL cells and macrophages. Angiogenesis and lymphangiogenesis have also been investigated.ResultsOX-40 expression promoted intravasation, metastasis, and cytokine secretion, and increased M2 macrophages. Additionally, it restores transendothelial migration and dissemination in the presence of M2 macrophages, possibly through ERK activation. Co-culture experiments revealed that OX-40 promoted a Th2 cytokine profile in CTCL, correlating with M2 macrophages in xenografts. Although OX-40 did not affect angiogenesis in this model, it promoted lymphangiogenesis via VEGF-C expression.DiscussionUsing the CTCL spontaneous metastasis model in chick embryos, we demonstrated that OX-40 regulates the TME to promote M2 increase, lymphangiogenesis, CAM intravasation, and metastasis. Therefore, the in vivo chick embryo metastasis model may serve as a valuable preclinical tool for identifying novel anti-tumor targets in CTCL. The OX-40 axis was identified as a key driver of CTCL progression, promoting tumor growth and metastasis through ERK activation while validating the chick embryo model as a preclinical tool for therapeutic testing.